My left foot - Sheridan, Jim, 1949-; Day-Lewis, Daniel; McAnally, Ray.; Fricker, Brenda; Bernstein, Elmer; Miramax Films; Buena Vista Home Entertainment (Firm) ([United States] : Miramax ; Burbank, CA : Distributed by Buena Vista Home Entertainment, 2005)
The story of Christy Brown, who was born with cerebral palsy. He learned to paint and write with his only controllable limb - his left foot.
DVD, region 1, widescreen (1.85:1) presentation; Dolby Digital 5.1 surround sound.
English dialogue or French language track with French or Spanish subtitles.
Title from container.
Daniel Day-Lewis, Ray McAnally, Brenda Fricker, Fiona Shaw, Adrian Dunbar.
Director of photography, Jack Conroy ; music, Elmer Bernstein.
Originally released as a motion picture in 1989.
Keywords: Brown, Christy, -- 1932-1981 -- Drama; Cerebral palsied -- Drama; Parâalisis cerebral -- Teatro; Brown, Christy, -- 1932-1981 -- Drama; Feature films; Disability -- Feature